Systematic review on Marburg virus prevalence and persistence in animals - Odoom, Theophilus; El-Duah, Philip; Dumevi, Rexford Mawunyo; Muzeniek, Therese; Tasiame, William; Abbiw, Richard Kwamena; Agyei, George; Aryeetey, Sherihane; Amuasi, John; Oladayo, Faleke Olufemi; Folitse, Raphael; Emikpe, Benjamin; et al. (Frontiers in Veterinary Science, 2026)
IntroductionMarburg Virus Disease (MVD) is a fatal zoonotic disease of humans and nonhuman primates caused by the Marburg virus (MARV) of the Filoviridae family, and presenting as hemorrhagic fever with a high fatality rate. Egyptian fruit bats, Rousettus aegyptiacus, are the principal natural reservoir, with evidence linking them to most human outbreaks.MethodsThis systematic review evaluated the prevalence of MARV in bats, domestic animals, and rodents, as well as the duration of antibodies and potential routes of viral shedding. A comprehensive search of six (6) scientific databases identified 30 studies meeting the inclusion criteria.ResultsIn bats, seroprevalence ranged from less than 1% to about 54% while MARV genes were detected in 0.8–3% of samples. MARV antibodies persisted for up to 11months in naturally infected bats, while induced or maternal antibodies declined within 5 months. Apart from Rousettus aegyptiacus, occasional seropositivity was detected in other bat species such as Epomops franqueti, Micropteropus pusillus, Hypsignathus monstrosus, and Eidolon helvum, whereas MARV particles were observed in Rousettus aegyptiacus and Hipposideros spp. Even though viral genes were undetected in domestic animals, non-human primates (NPH) and rodents, antibodies were reported in dogs and livestock, and NPH in Ghana and Gabon and Zambia, respectively, indicating a higher probability of non-lethal MARV exposure in these species.DiscussionThese findings confirm Rousettus aegyptiacus as the primary reservoir but suggest that other bats and domestic animals may contribute to the natural maintenance of MARV. Expanded multispecies surveillance in high-risk regions is essential to clarify reservoirs, host distribution, and transmission dynamics. Understanding these patterns is critical for designing targeted interventions to reduce spillover risk to humans.